540. Prolonged Viral Shedding of SARS-CoV-2 In Solid Organ Transplant Recipients. (31st December 2020) - Nam, Hannah; Roberts, Scott C; Tanna, Sajal D; Ison, Michael G
Abstract: Background: Solid organ transplant (SOT) recipients are more susceptible to viral infection and present with differing viral kinetics when compared to non-immunocompromised cohorts. The duration of viral shedding in SOT recipients with SARS-CoV-2 infection is unknown. Methods: All SOT recipients with a diagnosed of SARS-CoV-2 by nasopharyngeal of bronchoalveolar lavage RT-qPCR from March 06, 2020 to May 31, 2020 were identified. Viral shedding duration was obtained by evaluating all subsequent SARS-CoV-2 PCR results following initial positivity over time. Severity classification was defined as mild (outpatient), moderate (hospitalized), and severe (ICU level care). Data were obtained from electronic medical record case review and analyzed with Stata 16. Results: 71 patients with a positive SARS-CoV-2 PCR test were identified. 50 (70.4%) were classified as mild/moderate disease, while 21 (29.5%) had severe disease. Median age was 56.5 (IQR 45 – 61.3) years, and 56.9% (n = 41) were male. Older age was significantly associated with severe disease. A disproportionate number of patients were African American/Black or Hispanic at 72.2% (n=52). Interestingly, Caucasian race was significantly associated with less severe outcomes (p=0.038). The majority of patients were kidney transplant recipients (46, 63.9%), followed by liver (13, 18.1%), heart (6, 8.3%), lung (3, 4.2%), and pancreas (9, 12.5%) with a median duration from transplantation at 5 (IQR 3 – 17) years. Overall mortality was 5.6% (n=4), with all deaths occurring only in those with severe disease (19.1%, n=4). Prolonged viral shedding was observed in few patients, with median duration of SARS-CoV-2 PCR positivity at 32 (IQR 18.5 – 41.0) days. One kidney recipient was observed with up to 64 days of positive SARS-CoV-2 RT-PCR from initial diagnosis despite not developing severe disease. Demographics and Outcomes Duration of Viral Shedding in SOT Patients with COVID-19 Conclusion: COVID-19 can lead to significant outcomes in SOT with increased mortality in those with severe disease, as well as prolonged viral shedding. Further studies are needed to elucidate the full duration of viral shedding in this population. Disclosures: Michael G. Ison, MD MS, AlloVir (Consultant)